2019
DOI: 10.1017/aer.2019.70
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and lateral aerodynamic characterisation of reflex wing Unmanned Aerial Vehicle from flight tests using Maximum Likelihood, Least Square and Neural Gauss Newton methods

Abstract: In this paper, longitudinal and lateral-directional aerodynamic characterisation of the Cropped Delta Reflex Wing (CDRW) configuration–based unmanned aerial vehicle is carried out by means of full-scale static wind-tunnel tests followed by full-scale flight testing. A predecided set of longitudinal and lateral/directional manoeuvres is performed to acquire the respective flight data, using a dedicated onboard flight data acquisition system. The compatibility of the acquired dynamics is quantified, in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Some of the longitudinal and lateral-directional parameters of both CDFP and CDRW UAVs have already been estimated using wind tunnel testing in Refs [40][41][42]. The parameters estimated using FEM and FEM-PSO are compared against the corresponding wind tunnel estimates for both CDFP and CDRW.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the longitudinal and lateral-directional parameters of both CDFP and CDRW UAVs have already been estimated using wind tunnel testing in Refs [40][41][42]. The parameters estimated using FEM and FEM-PSO are compared against the corresponding wind tunnel estimates for both CDFP and CDRW.…”
Section: Resultsmentioning
confidence: 99%
“…However in the case of UAVs, the availability of research related to the aerodynamic characterisation from flight data is minimal due to their classified applications. EEM is one of the simplest and computationally efficient flight test methods to estimate flight vehicle aerodynamic stability and control derivatives from flight test data [29]. However, the formulation of EEM restricts its application in estimating aerodynamic parameters from flight data pertaining to near stall and high angle-of-attack manoeuvers.…”
Section: Introductionmentioning
confidence: 99%
“…It is well observed that both methods require priory information about initial conditions for better convergence and confidence of solutions. On the contrary, the AI estimation method based on Neural Networks does not require priory information about initial conditions and can be used to characterise the aerodynamic behaviour of a UAV in linear and nonlinear flight regimes [29,31]. In general, the Neural Networks estimation method is based on OEM requires gradient computation to update the weights of networks, which makes it a high computational effort demanding method.…”
Section: Introductionmentioning
confidence: 99%
“…Two major techniques that have been widely used and well developed are the time-domain identification and the frequency-domain identification (10) . The Maximum Likelihood (ML) method is by far the most commonly used time-domain technique for estimating parameters from dynamic flight data (14,(16)(17)(18) . Previously, Saderla et al (12,17) efficiently applied the ML together with Gauss Newton (GN) method to estimate longitudinal and lateral-directional parameter for Unmanned Aerial Vehicle (UAV).…”
Section: Introductionmentioning
confidence: 99%
“…The Maximum Likelihood (ML) method is by far the most commonly used time-domain technique for estimating parameters from dynamic flight data (14,(16)(17)(18) . Previously, Saderla et al (12,17) efficiently applied the ML together with Gauss Newton (GN) method to estimate longitudinal and lateral-directional parameter for Unmanned Aerial Vehicle (UAV). Verma and Peyada (18) utilized the extreme learning machine based to extract the stability and control derivatives of the all composites HANSA-3 aircraft using the real flight test data.…”
Section: Introductionmentioning
confidence: 99%